FEP encapsulated crack-based sensor for measurement in moisture-laden environment - Kim, Minho; Choi, Hyesu; Kim, Taewi; Hong, Insic; Roh, Yeonwook; Park, Jieun; Seo, Sung Chul; Han, Seungyong; Koh, Je sung; Kang, Daeshik (Materials, 2019)
Among many flexible mechanosensors, a crack-based sensor inspired by a spider's slit organ has received considerable attention due to its great sensitivity compared to previous strain sensors. The sensor's limitation, however, lies on its vulnerability to stress concentration and the metal layers' delamination. To address this issue of vulnerability, we used fluorinated ethylene propylene (FEP) as an encapsulation layer on both sides of the sensor. The excellent waterproof and chemical resistance capability of FEP may effectively protect the sensor from damage in water and chemicals while improving the durability against friction.
Keywords: Encapsulation layer; Fluorinated ethylene propylene; Mechanosensors; Metal layer; Spider inspired; Strain sensors; Thin metal films; Crack; Encapsulation; Spider inspired; Strain sensor; Thin metal film